The N-Acetylglucosaminidase LytB of Streptococcus pneumoniae Is Involved in the Structure and Formation of Biofilms - Domenech, Mirian (Appl Environ Microbiol, 2020)
The N-acetylglucosaminidase LytB of Streptococcus pneumoniae is involved in nasopharyngeal colonization and is responsible for cell separation at the end of cell division; thus, ΔlytB mutants form long chains of cells. This paper reports the construction and properties of a defective pneumococcal mutant producing an inactive LytB protein (LytB(E585A)). It is shown that an enzymatically active LytB is required for in vitro biofilm formation, as lytB mutants (either ΔlytB or producing the inactive LytB(E585A)) are incapable of forming substantial biofilms, despite that extracellular DNA is present in the biofilm matrix. Adding small amounts (0.5 to 2.0 μg/ml) of exogenous LytB or some LytB constructs restored the biofilm-forming capacity of lytB mutants to wild-type levels. The LytB(E585A) mutant formed biofilm more rapidly than ΔlytB mutants in the presence of LytB. This suggests that the mutant protein acted in a structural role, likely through the formation of complexes with extracellular DNA. The chain-dispersing capacity of LytB allowed the separation of daughter cells, presumably facilitating the formation of microcolonies and, finally, of biofilms. A role for the possible involvement of LytB in the synthesis of the extracellular polysaccharide component of the biofilm matrix is also discussed. IMPORTANCE It has been previously accepted that biofilm formation in S. pneumoniae must be a multigenic trait because the mutation of a single gene has led to only to partial inhibition of biofilm production. In the present study, however, evidence that the N-acetylglucosaminidase LytB is crucial in biofilm formation is provided. Despite the presence of extracellular DNA, strains either deficient in LytB or producing a defective LytB enzyme formed only shallow biofilms.